Between Drama and Postdrama - Pukelytė, Ina (Respectus Philologicus, 2016)
The article analyses the transformations of the genre of drama in the context of the postdramatic theatre. Contrary to the affirmations of Hans-Thies Lehmann, the main theoretician of the postdramatic theatre, a text of a drama is not always only one of the elements of the postdramatic theatre. A text of a drama is often the main axis of a performance, around which it is constructed. It is presumed that the postdramatic theory allows a new approach to the genre of drama and encourages the birth of texts that can be called postdramas. The example of a performance of Wartists is aimed to show that the text of this performance can be treated as a postdrama, since it is caused not by a playwright but by a creative collaboration between the director, the actors and the playwright. The result of this collaboration is a text that integrates very different strategies of the creation of drama. There is an evidence of a play with different drama forms: epic, social, documental media, cruelty, Brecht’s theatre, theatre in the theatre, stand up or intermezzo. It can be assumed that drama, which in the postmodern theatre played only a secondary role, becomes postdrama and the contemporary theatre. It renews itself while using the strategies that are common in the postdramatic theatre, which means that it integrates various aesthetics common for this theatre and obliges them to serve as a text.
Keywords: postdrama; Marius Ivaškevičius; Wartists